Forest Remnants: Conserving and Observing Bird Diversity in Urban Settings - Dan Dawson; Mark Hostetler (EDIS)
WEC298, a 7-page illustrated fact sheet by Dan Dawson and Mark Hostetler, discusses urban forest remnant design and management as it relates to bird conservation. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, September 2010.